2022
DOI: 10.3389/fimmu.2022.1030222
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals TCR+ macrophages in HPV-related head and neck squamous cell carcinoma

Abstract: The prognosis of human papillomavirus (HPV)-infected head and neck squamous cell carcinoma (HNSCC) is often better than that of HPV- cancer, which is possibly caused by the differences in their immune microenvironments. The contribution of macrophage, as a principal innate immune cell, to this phenomenon is still unclear. In this study, a single-cell atlas of 4,388 high-quality macrophages from 18 HPV- and 8 HPV+ HNSCC patients was constructed with single-cell RNA sequencing data. Eight macrophage subsets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Cells expressing FABP5 , a marker for lipid‐rich foamy macrophages, 23 were enriched in C3, suggesting that they could be lipid‐laden foam macrophages. In concordance with a previous report 24 there was a distinct subcluster (C6) with enrichment of cells expressing the T cell marker gene ( CD3D ) and TCR marker genes TRAC (Figure 4A,E), suggesting that they could be CD3 + TCR + macrophage cell populations.…”
Section: Resultssupporting
confidence: 92%
“…Cells expressing FABP5 , a marker for lipid‐rich foamy macrophages, 23 were enriched in C3, suggesting that they could be lipid‐laden foam macrophages. In concordance with a previous report 24 there was a distinct subcluster (C6) with enrichment of cells expressing the T cell marker gene ( CD3D ) and TCR marker genes TRAC (Figure 4A,E), suggesting that they could be CD3 + TCR + macrophage cell populations.…”
Section: Resultssupporting
confidence: 92%
“…These two clusters, especially macroC3, also had high expression of KRT19, which may be the reason for their radioresistance 39 . Interestingly, macroC4 had high expression of CD3D and CD3E, which can activate TCR signalling 40 . We found that the number of TCR clonotypes of macroC4 was reduced in recurrent chordomas (Figures 3E and S14).…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, this population of macrophages also has higher expression of OLR1 , a marker of myeloid-derived suppressor cells (MDSC) in other tumors [40]. Macrophages expressing T-cell marker genes have been previously found in inflammatory diseases and head and neck squamous cell carcinoma [41, 42], however, their role in the OS TME is unclear.…”
Section: Resultsmentioning
confidence: 99%